Exploring the effect of the LnIII/LnII redox potential on C–F activation and on oxidation of some lanthanoid organoamides. Issue 4 (17th December 2015) - Deacon, Glen B.; Junk, Peter C.; Kelly, Rory P.; Wang, Jun
Abstract : The role of the Ln II oxidation state (Ln = Eu, Yb, Sm) in C–F activation reactions has been explored. Abstract : The divalent europium complexes, [Eu(L Me/Et )2 (thf)2 ] and[Eu(L Et )2 (dme)] (L Me/Et = p -HC6 F4 N(CH2 )2 NMe2 /Et2 ), have been prepared from redox-transmetallation/protolysis (RTP) reactions between Eu metal, Hg(C6 F5 )2 and L Me/Et H in thf. The complexes exhibit close (C)F–Ln interactions and the amide ligands feature tridentate N, N ′, F chelation. The complexes are thermally robust but on exposure to light they undergo C–F activation. From exposure of[Eu(L Et )2 (thf)2 ] to light, the Eu III mixed fluoride/oxide cluster, [Eu4 (L Et )6 F2 O2 ] was isolated, but other well-defined C–F activation products have proven elusive due to the stability of Eu II . Oxidation of [Ln(L R )2 (thf)2 ] (Ln = Eu, R = Me; Ln = Yb, R = Et) with I2 afforded the heteroleptic iodo complexes, [Ln(L R )2 I(thf) n ] (Ln = Eu, n = 1; Ln = Yb, n = 0), and the homoleptic complexes, [Ln(L R )3 ]. The formation of the iodo complexes and the heteroleptic complexes appear to occur by different routes.[Yb(L Et )3 ] shows interesting structural differences from reported [Ln(L Et )3 ] (Ln = La, Ce, Nd) complexes, and highlights an incomplete shift towards N, N ′ chelation to the much smaller Yb ion.[Sm(L Me )3 ] was prepared from a protolysis reaction between [Sm(CH2 C6 H4 -NMe2 - o )3 ] and L Me H. Heating a solution of[Sm(L Me )3 ] in toluene at 110 °C for three days did not afford any samarium fluoride complex. An RTP reaction with Sm afforded the heteroleptic samarium complex, [Sm(L Me )2 F]3, in very low yield. From an attempted protolysis reaction between [Sm(DippForm)2 (thf)2 ] and L Me H, the mixed ligand samarium fluoride complex, [Sm(DippForm)(L Me )F]2, was isolated. Overall, the instability of Sm II precludes control over the C–F activation reactions.